Abdominal Aortic Aneurysmectomy in Renal Transplant Patients - Jebara, Victor A. (1990)
Because renal transplantation is allowing an increased number of patients to survive for prolonged periods, abdominal aortic aneurysms can be expected to occur with growing frequency in these patients. Surgical management of such cases involves the provision of allograft protection. To date, the literature contains 15 reports of abdominal aortic aneurysms in renal allograft recipients. We describe a 16th case and discuss the management of these patients. (Texas Heart Institute Journal 1990;17:240-4)